Fines extracted from recycled concrete as alternative raw material for Portland cement clinker production. (April 2015) - Schoon, Joris; De Buysser, Klaartje; Van Driessche, Isabel; De Belie, Nele
Abstract: This paper aims to examine the use of fines generated out of recycled aggregates production as an alternative raw material for Portland clinker kilns with enumeration of possible limitations. Different technical set-ups were used to separate these fines from the recycled aggregates. The relationship between the particle size distribution of the generated fines fraction and their chemical composition as well as the relationship between the final filler (<63 μm) content [ wt% ] and the water demand of the treated sand fraction were investigated. Numerical simulations were carried out to maximise the fines fractions as raw materials in clinker kilns based on which experimental clinkers were produced. The final clinkers were fully analysed and evaluated on possible mineralogical influences.